Dr. Zsuzsanna Ignacz — Deep Plane Facelift — Budapest - Ignacz, Zsuzsanna (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Zsuzsanna Ignacz, practicing in Budapest, Hungary. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003256; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; hungary; budapest